2013
DOI: 10.3389/fpubh.2013.00065
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Variations in Preventive Dental Care Utilization among Middle-Aged and Older Americans, 1999–2008

Abstract: Objective: This study examined recent trends of preventive dental care utilization among Americans aged 50 and above, focusing on variations across racial and ethnic groups including Whites, Blacks, Hispanics, American Indians/Alaska Natives, and Asians.Methods: Self-reported information on oral health behaviors was collected from 644,635 participants in the Behavioral Risk Factor Surveillance System between 1999 and 2008.Results: Despite a significant upward trend of frequency of dental cleaning from 1999 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…In an unadjusted analysis, lower OHL was found in racial minorities, those with lower education, unemployed or disabled individuals, single individuals, and those without a regular source of primary care or without dental insurance. These results are not surprising given that disparities among racial and ethnic minorities, men, low-income, and uninsured individuals are well documented [11,12,13,14,15,16,17,18,19]. Prior studies have reported on the effectiveness of educational interventions for improving oral health [31].…”
Section: Discussionmentioning
confidence: 95%
“…In an unadjusted analysis, lower OHL was found in racial minorities, those with lower education, unemployed or disabled individuals, single individuals, and those without a regular source of primary care or without dental insurance. These results are not surprising given that disparities among racial and ethnic minorities, men, low-income, and uninsured individuals are well documented [11,12,13,14,15,16,17,18,19]. Prior studies have reported on the effectiveness of educational interventions for improving oral health [31].…”
Section: Discussionmentioning
confidence: 95%
“…Despite the limitations, the current study went beyond that of prior research by including a reliable dental insurance variable while the previous studies used medical insurance as a proxy for dental insurance [12,30]. It is found that using medical insurance in place of dental insurance will lead to inaccurate results since private medical insurance does not cover dental care [12].…”
Section: Discussionmentioning
confidence: 97%
“…In general terms, research focused on the accessibility of oral health services in Colombia and developing countries are scarce (de la Fuente-Hernández et al, 2010;Matos & Lima-Costa, 2007;Pilger et al, 2011;Wu et al, 2013). Studies conducted in Brazil found that the elderly tend to seek out oral health services in low frequency (Matos & Lima-Costa; Pilger et al).…”
Section: Discussionmentioning
confidence: 99%